KARAKTERISTIK COOKIES DENGAN VARIASI TERIGU DAN TEPUNG PISANG TANDUK PREGELATINISASI - Siswanto, Vesta; Sutedja, Anita Maya; Marsono, Yustinus (Jurnal Teknologi Pangan dan Gizi, 2015)
Processing Musa corniculata into banana flour can increase the diversification of banana utilization, extend shelf life and improve its economical value. One of the diversified product of banana flour is cookies. Utilization of banana flour in the production of cookies has another advantage i.e. reduction of wheat flour. However, the banana flour might result starchy aftertaste to the product. To reduce theunpreferable taste, it is proposed to use pregelatinize banana flour instead of unpregelatinized banana flour. The proportion of wheat flour and pregelatinized Musa corniculata flour will affect cookies characteristic so we need to know the exact proportion. Research using randomized block design with the treatment is proportion wheat flour and pregelatinized Musa corniculata flour. (100:0), (80:20), (60:40), (40:60), (20:80) and (0:100). The results showed that the difference in the proportion of significant effect on the physicochemical characteristics (moisture content, specific volume, power broken, and color) and organoleptic (color, flavor, aroma, crispness, broken power and mouthfeel). Cookies with proportion 60:40 give the best characteristic.